Modeling and simulation of a wind induction solar tower for electric power generation - الحايك رائد; جابر ديبة (Latakia University Journal -Engineering Sciences Series, 2023)
A comprehensive theoretical study was presented for each of the three main components of the solar chimney with an evaluation of the theoretical performance in the solar towers in addition to the design and study of a small practical model on the ground with the study of the factors affecting it such as the effect of the intensity of solar radiation, the height of the solar chimney, the diameter of the solar collector and the thermal conductivity coefficient of the collector cover . The various mathematical equations controlling the solar chimney were studied with some special assumptions that were adopted, where the performance of the system depends on several factors and different criteria, including the surrounding conditions such as radiation and temperatures, as well as the location and structural dimensions of the system such as the height of the chimney and the radius of the solar collector, the materials used and their physical properties, The energy produced directly depends on these equations, which together constitute an integrated unit to explain the system, and then the project was modeled using the EES program and Solidworks program to study and draw the mini-model.